Microstructural investigation supporting an abrupt stress induced transformation in amorphous carbon films - PEROVA, TANIA (American Institute of Physics, 2009)
The intrinsic stress of carbon thin films deposited by filtered cathodic arc was investigated as a function of ion energy and Ar background gas pressure. The microstructure of the films was analyzed using transmission electron microscopy, electron energy loss spectroscopy, and Raman spectroscopy. The stress at given substrate bias was reduced by the presence of an Ar background gas and by the presence of a Cu underlayer deposited onto the substrate prior to deposition. Auger electron spectroscopy depth profiles showed no evidence of Ar incorporation into the films. A sharp transition from a sp2 to sp3 rich phase was found to occur at a stress of 6.5?1.5 GPa, independent of the deposition conditions. The structural transition at this value of stress is consistent with available data taken from the literature and also with the expected value of biaxial stress at the phase boundary between graphite and diamond at room temperature. The microstructure of films with stress in the transition region near 6.5 GPa was consistent with a mixture of sp2 and sp3 rich structures.
PUBLISHED
Keywords: Electronic & Electrical Engineering